Teaching the Privileged? Observations on the (UN) Inclusiveness of Online Education during Pandemic - Nashia Ajaz (PJDOL, 2021)
Coronavirus pandemic has changed the existing norms of life all over the world. Among other areas of life, the pandemic has also hit the education sector, where recent statistics show that around 500 Million students worldwide were unable to access remote learning. In developing countries like Pakistan, which is amongst the top-twenty countries impacted by the pandemic, and where around 23 million children were already out of school, much of the progress made over the years has reversed.